The Learning Hub – Empowering Remote Rural Communities across India through Blended Learning - Mehta, Aarsh; Barfield, Ana; Thomson, Mark (International Journal of Advanced Corporate Learning (iJAC), 2024)
This case study explores The Learning Hub, an initiative of the Aga Khan Foundation (AKF), which hosts, among many other learning assets, a three-strand learning programme to enhance the quality of life in rural India through innovative blended learning strategies. The programme, delivered by the Aga Khan Rural Support Programme India (AKRSPI), addresses critical issues such as water sanitation, sustainable agriculture, and governance by delivering courses through a combination of video-based online content and in-person facilitation. The study provides a brief analysis of AKF's blended learning approach, and its impact on community resilience, economic development, and social equity.